Enzyme kinetics and inhibition parameters of human leukocyte glucosylceramidase - Mesut Karatas; Senol Dogan; Emrulla Spahiu; Adna Ašić; Larisa Bešić; Yusuf Turan (Heliyon, 2020)
Glucosylceramidase (GCase) is a lysosomal enzyme that catalyzes the cleavage of β-glucosidic linkage of glucocerebroside (GC) into glucose and ceramide; thereby, plays an essential function in the degradation of complex lipids and the turnover of cellular membranes.The growing list of 460 mutations in the gene coding for it—glucosylceramidase beta acid 1 (GBA1)—is reported to abolish its catalytic activity and decrease its enzyme stability, associating it with severe health conditions such as Gaucher disease (GD), Parkinson Disease (PD) and Dementia with Lewy bodies (DLB).Although the three-dimensional structure of wild type glucosylceramidase is elucidated, little is known about its features in human cells. Moreover, alternative sources of GCase that prove to be effective in the treatment of diseases with enzyme treatment therapies, impose the need for a simple and cost-effective procedure to study the enzyme behavior. This work, for the first time, shows a well-established, yet simple, cost- and time-efficient protocol for the study of GCase enzyme in human leukocytes by the artificial substrate p-Nitrophenyl-β-D-glucopyranoside (PNPG). Characterization of the enzyme in human leukocytes for activation parameters (optimal pH, Km, and Vmax) and enzyme inhibition was done. The results indicate that the optimum pH of GCase enzyme with PNPG is 5.0. The Km and Vmax values are 12.6mM and 333 U/mg, respectively. Gluconolactone competitively inhibits GCase, with a Ki value of 0.023 mM and IC50 of 0.047 mM. Glucose inhibition is uncompetitive with a Ki of 1.94 mM and IC50 of 55.3 mM. This is the first report for the inhibitory effect of glucose, δ-gluconolactone on human leukocyte GCase activity.